A Systems Thinking for Hotel Tax Optimization: Evidence from Tourism Dynamics in Garut Regency - Muslim Alkautsar; Tinneke Hermina; Hanifah Hanifah; Marizsa Herlina; Hanifah Fauziah (Yayasan Ilomata, 2026)
The growth of the tourism sector does not necessarily translate into stronger local fiscal performance. In Kabupaten Garut, hotel tax revenue, despite its close relationship with tourism activities, has not fully reflected its potential contribution to local own-source revenue (PAD). This study aims to analyze hotel tax revenue performance based on effectiveness, growth stability, and contribution to local tax revenue, while identifying strategies to optimize revenue through potential-based target setting, digital monitoring systems, and the integration of tourism and fiscal policies. In this study, optimization refers to improving target accuracy, taxpayer compliance, and sustainable revenue growth. A mixed-methods approach was employed by combining quantitative descriptive analysis with systems thinking. Quantitative analysis measured effectiveness ratios, annual growth rates, and contribution levels using secondary data for the 2015–2022 period. Qualitative data were obtained through semi-structured interviews with officials from the Regional Revenue Agency (BAPENDA) and hotel taxpayers to identify structural constraints and construct a causal loop diagram. The findings indicate that effectiveness ratios exceeded 100% in most years, except in 2017 (90%), demonstrating generally effective tax collection. However, revenue growth remained highly volatile, ranging from –31.52% in 2020 to 52.06% in 2022. Hotel tax contributed an average of 6.72% to total local tax revenue, indicating a moderate fiscal role despite tourism expansion. Institutional capacity limitations, uneven digital system implementation, and taxpayer compliance challenges remain key barriers. The study concludes that sustainable hotel tax optimization requires potential-based target setting, integrated digital monitoring, and stronger coordination between tourism development and local fiscal policy.